If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x) * 4 + 13 = 37 Reorder the terms for easier multiplication: 4x + 13 = 37 Reorder the terms: 13 + 4x = 37 Solving 13 + 4x = 37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4x = 37 + -13 Combine like terms: 13 + -13 = 0 0 + 4x = 37 + -13 4x = 37 + -13 Combine like terms: 37 + -13 = 24 4x = 24 Divide each side by '4'. x = 6 Simplifying x = 6
| 7x+1.9=2x+0.3 | | =x*33[34] | | 8V+13=3V+38 | | x+(2x-18)=90 | | a+78=168 | | 7x-12-3x=8x-9 | | 4x=144x | | y=10-7x | | 5-2=4how | | 6x^2+22+2x^2+50=60 | | (x-3)=-4x+27 | | -5+x=-21 | | 5.8(x-2)=-0.2x+30.4 | | -5+x=21 | | 6(x-4)+72=-2x | | y-20=-7 | | 10(1-y)= | | 5x+3-7x=2x-5 | | t-46=40 | | 16-(6-3)= | | x*5=x*10-10 | | -12(x-7)=3(x-17) | | g=-5 | | 6,5x=2+5,5x | | 9-x=0,16*(30-x) | | -120-7x=10+16 | | 2x^2-179=0 | | 3x+40=11x-32 | | 9r^2+18r-7=0 | | 6x+42=10x-10 | | r=4.3m | | 2(3+2x)-4=8 |